2012
DOI: 10.1021/ja305321e
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Asymmetric Synthesis of All-d-, All-l-, and d-/l-Oligosaccharides Using Atom-less Protecting Groups

Abstract: Oligosaccharide synthesis is hindered by the need for multiple steps as well as numerous selective protections and deprotections. Herein we report a highly efficient de novo route to various oligosaccharide motifs, of use for biological and medicinal structure activity studies. The key to the overall efficiency is the judicious use of asymmetric catalysis and synthetic design. These green principles include the bidirectional use of highly stereoselective catalysis (Pd(0)-glycosylation/post-glycosylation). In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 52 publications
0
56
0
Order By: Relevance
“…Inspired by the role of 6-hydroxy-3-pyranones as key intermediates for carbohydrate synthesis, [10] ODoherty [11] and co-workers have disclosed an elegant palladium-catalyzed stereospecific glycosidation [11][12][13] of 3-pyranones with an ester substituent in the 5-position (Scheme 1a)f or assembling diversified libraries [14] and complex natural products. [15] Because of the significance of pyranones with as ubstituent (e.g.,e sters) in the 6-position, many efforts have been devoted to the manipulation of the hemiacetal group of pyranones,for example,bythe protection or oxidation of the hemiacetal group.…”
mentioning
confidence: 99%
“…Inspired by the role of 6-hydroxy-3-pyranones as key intermediates for carbohydrate synthesis, [10] ODoherty [11] and co-workers have disclosed an elegant palladium-catalyzed stereospecific glycosidation [11][12][13] of 3-pyranones with an ester substituent in the 5-position (Scheme 1a)f or assembling diversified libraries [14] and complex natural products. [15] Because of the significance of pyranones with as ubstituent (e.g.,e sters) in the 6-position, many efforts have been devoted to the manipulation of the hemiacetal group of pyranones,for example,bythe protection or oxidation of the hemiacetal group.…”
mentioning
confidence: 99%
“…We have demonstrated that a de novo approach to carbohydrates 6 can be used for the assembly and medicinal chemistry study of oligosaccharides. 7, 8 The approach combines the use of asymmetric synthesis of pyranone glycosyl donor 5 , a Pd(0)-catalyzed glycosylation and post-glycosylation transformation, which allow the enone functionality of the pyranones to serve as atom-less protecting groups for the C -2 to C -4 triol portion of the target rhamno -pyranose. Because the route uses asymmetric synthesis, it offers equal efficiency to access to various all D-, all L- and mixed D/L-isomer.…”
mentioning
confidence: 99%
“…As we have previously reported, Boc‐pyranones 9a and 9b were obtained optically pure from furans 1a and 1b in three steps by Noyori atom‐transfer asymmetric reduction13 [formic acid/Et 3 N, ( R )‐Ru(η 6 ‐mesitylene)‐( S , S )‐TsDPEN], Achmatowicz cyclization (NBS, H 2 O), and tert ‐butoxycarbonylation with Boc 2 O (Scheme ) 14. Palladium‐catalyzed glycosylation with benzyl alcohol resulted in benzyl pyranones 2a and 2b .…”
Section: Resultsmentioning
confidence: 93%